Ytterbium oxide as radiopacifier of calcium silicate-based cements. Physicochemical and biological properties - Costa, Bernardo Cesar [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Bosso-Martelo, Roberta; Rodrigues, Elisandra Márcia [UNESP]; Bonetti-Filho, Idomeo [UNESP]; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2018)
This study evaluated physicochemical properties, cytotoxicity and bioactivity of MTA Angelus (MTA), calcium silicate-based cement (CSC) and CSC with 30% Ytterbium oxide (CSC/Yb 2 O 3 ). Setting time was evaluated using Gilmore needles. Compressive strength was evaluated in a mechanical machine. Radiopacity was evaluated using radiographs of materials and an aluminum scale. Solubility was evaluated after immersion in water. Cell viability was evaluated by means of MTT assay and neutral red staining, and the mineralization activity by using alkaline phosphatase activity and Alizarin Red staining. The data were submitted to ANOVA, Tukey and Bonferroni tests (5% significance). The bioactive potential was evaluated by scanning electron microscopy. The materials presented similar setting time. MTA showed the lowest compressive strength. MTA and CSC/Yb 2 O 3 presented similar radiopacity. CSC/Yb 2 O 3 showed low solubility. Saos-2 cell viability tests showed no cytotoxic effect, except to 1:1 dilution in NR assay which had lower cell viability when compared to the control. ALP at 1 and 7 days was similar to the control. MTA and CSC had greater ALP activity at 3 days when compared to control. All the materials present higher mineralized nodules when compared with the control. SEM analysis showed structures suggesting the presence of calcium phosphate on the surface of materials demonstrating bioactivity. Ytterbium oxide proved to be a properly radiopacifying agent for calcium silicate-based cement since it did not affected the physicochemical and biological properties besides preserving the bioactive potential of this material.
Keywords: Cell survival; Endodontic; Physicochemical analysis; Silicate cement; Ytterbium